2001
DOI: 10.1097/00042737-200108000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis serum induces a nitric oxide-associated vascular hyporeactivity of aortic segments from healthy rats in vitro

Abstract: Cirrhotic serum decreases the contractile response to phenylephrine even in an early stage of secondary cirrhosis. Reversibility of this effect after nitric oxide synthesis blockade suggests an induction of nitric oxide synthesis by systemic factors as a major point in vascular hyporeactivity to vasoconstrictors in cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Taking into account that upon HSV intranasal infection, we observed that in the lungs these cells stain positively for NOS-II, we decided to investigate if they were susceptible to AG inhibition of NO production. AG has been widely used as selective inhibitor of NOS-II activity [Gardiner et al, 1996;Lecanu et al, 1998;Guc, 1999;Neufeld et al, 1999Neufeld et al, , 2002Schmandra et al, 2001]. First, we observed that AG treatment was able to block, in a dose-dependent way, LPS plus IFN-g-induced NO production in cultures of cells obtained from bronchoalveolar washings (Fig.…”
Section: Ag Inhibits No Production In Vitro and Ex Vivomentioning
confidence: 70%
See 1 more Smart Citation
“…Taking into account that upon HSV intranasal infection, we observed that in the lungs these cells stain positively for NOS-II, we decided to investigate if they were susceptible to AG inhibition of NO production. AG has been widely used as selective inhibitor of NOS-II activity [Gardiner et al, 1996;Lecanu et al, 1998;Guc, 1999;Neufeld et al, 1999Neufeld et al, , 2002Schmandra et al, 2001]. First, we observed that AG treatment was able to block, in a dose-dependent way, LPS plus IFN-g-induced NO production in cultures of cells obtained from bronchoalveolar washings (Fig.…”
Section: Ag Inhibits No Production In Vitro and Ex Vivomentioning
confidence: 70%
“…AG has been largely used as a selective NOS-II inhibitor [Gardiner et al, 1996;Lecanu et al, 1998;Guc, 1999;Neufeld et al, 1999Neufeld et al, , 2002Schmandra et al, 2001]. Mice were separated in different experimental groups according to the amount of AG received.…”
Section: Aminoguanidine (Ag) Treatment Of Infected Micementioning
confidence: 99%
“…Taking into account that upon antigen inoculation, we observed the expression of NOS-II in turbinates and lungs, we decided to investigate the effect of inhibiting NO production on the antigen-specific immune response. For this purpose, we decided to use AG, taking into account that this compound has been widely used as selective inhibitor of NOS-II activity [21][22][23][24][25][26][27][28]. We observed that AG treatment was able to block, in a dose-dependent way, LPS plus IFN-␥-induced NO production in cultures of cells obtained from pulmonar washings (Fig.…”
Section: Nos-2 Activation In Turbinates and Lungs Obtained From Inocumentioning
confidence: 99%
“…For this purpose, we used aminoguanidine (AG), a drug that has been largely used as a selective NOS-II inhibitor [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…NO has been widely implicated in the decreased vascular response to endogenous vasoconstrictors, a generalized phenomenon observed in clinical and experimental cirrhosis, in the setting of elevated circulating levels of vasoconstrictors [29,31,33,37,38], although the mechanisms by which this happens are not completely elucidated. The present study also shows a decrease in renal response to PHE at 15 and 21 days after BDL, coexisting with an increase in urinary nitrite excretion.…”
Section: Figure 6 Representative Nitrotyrosine Expression In the Innementioning
confidence: 99%